Network Governance Analysis in Accelerating Stunting Reduction in the Papua Mountains Province - Nataniel Immanuel Hadi; Thahir Haning; Muhammad Yunus; Gita Susanti (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study examines the role of network governance in accelerating stunting reduction in the Papua Mountains Province, one of the regions with the highest stunting prevalence in Indonesia. The research is motivated by the persistence of high stunting rates, reaching above 30 percent and approximately 37.5 percent in recent reports, significantly exceeding the national average. Using a qualitative approach through a literature review, this study analyzes various sources, including academic articles, government reports, and international publications. The findings reveal that stunting in the Papua Mountains Province is not only a health issue but also a multidimensional problem influenced by poverty, food insecurity, limited infrastructure, and geographical isolation. The network governance structure involves multiple actors across national and local levels, coordinated through the Stunting Reduction Acceleration Team (TPPS). However, the implementation remains largely administrative, with limited functional integration and fragmented collaboration among stakeholders. Barriers such as weak coordination, limited human resources, and unintegrated data systems further hinder policy effectiveness. Sociocultural factors, including traditional practices and low health literacy, also significantly influence program outcomes. The study concludes that strengthening network governance requires improved coordination, institutional capacity, data integration, and culturally adaptive, community-based approaches to achieve sustainable stunting reduction outcomes.